PENGARUH TEKNOLOGI INFORMASI DALAM PERMAINAN (GAME) UNTUK PERKEMBANGAN PENDIDIKAN ANAK YANG BERKUALITAS - Bibit Sudarsono (Universitas Bina Sarana Informatika, 2012)
The game is an excellent medium for the development of children in infancy in order to improveintelligence, creativity, skilled, honest and disciplined. But parents should assist in conductingactivities such games, because with the rise of the game online / offline makes children forgetthemselves for duty, which is well studied. And the role of the teacher as an educator who has thetask of building the character of their students, it is expected that the teachers keep abreast ofinformation technology is expected to become professional teachers. Of institutions and socialagencies that this government ministries and communications technologies that can monitor andcontrol the circulation of a lively game both online and offline service providers and the gameitself, so that the parents would not worry about child development, because the child does notirregularities at his age.Keywords: game for education, game online/offline, education